The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma12111852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turning Amount on Metallurgical Qualities and Mechanical Properties of GH4169 Superalloy

Abstract: The determination of an appropriate amount of turning for superalloy ingot surfaces, in a scientific and reasonable manner, is vital to the improvement of the metallurgical quality and comprehensive performance of superalloy ingots. In the present study, scanning electron microscopy with energy-dispersive spectroscopy, a high-temperature testing machine, a Brinell hardness tester and the Image-Pro Plus software were used to analyze and compare the types and amounts of inclusions, the average area of the (Al,Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The nickel-based superalloy GH4169 alloy has become a key material for aerospace applications due to its excellent comprehensive properties, and it is used to manufacture key components such as rocket engines and aeroengines [ 1 , 2 , 3 ]. The GH4169 alloy rings and thin-walled parts needed for manufacturing these components can exhibit a large deformation of residual stress due to uneven plastic deformation and temperature change during the hot working process, which will seriously reduce the dimensional accuracy of the parts, resulting in a large deviation between the size of the parts produced by hot working and the required size.…”
Section: Introductionmentioning
confidence: 99%
“…The nickel-based superalloy GH4169 alloy has become a key material for aerospace applications due to its excellent comprehensive properties, and it is used to manufacture key components such as rocket engines and aeroengines [ 1 , 2 , 3 ]. The GH4169 alloy rings and thin-walled parts needed for manufacturing these components can exhibit a large deformation of residual stress due to uneven plastic deformation and temperature change during the hot working process, which will seriously reduce the dimensional accuracy of the parts, resulting in a large deviation between the size of the parts produced by hot working and the required size.…”
Section: Introductionmentioning
confidence: 99%
“…There may be some evidence for the macroscopic depth of cracks. One study [7] has found evidence of oxygen (i.e., most probably overlooked oxide bifilms) at up to nearly 50 mm depth.…”
Section: Shelf Formationmentioning
confidence: 99%